The 'War' of Appropriate Pricing of Petroleum Products: The Discourse of Nigeria's Reform Agenda - Salami, Oladipo; Ayoola, Kehinde A. (Linguistik Online, 2010)
This study focuses on the newspaper coverage of the debate on the pricing of petroleum products (petroleum, diesel, kerosene, etc.) in Nigeria. It seeks to examine, specifically, the discursive constructions of economic development with particular concern for the reform agenda in the country's petroleum sector. In doing this, the paper tries to analyze and characterize the debate on the increase in the prices of petroleum products in the country between 1999 and 2004; following on the heels of World Bank and International Monetary Fund (IMF)-driven reforms. It further situates the analysis of the debate within the history and politics of oil and development in the country with particular concern for the 'angles of telling' of the participants. Using the framework of critical discourse analysis (CDA), the paper attempts to show the ideological elements in the discourse of socio-political development in Nigeria as constructed by the different sociopolitical groups and concludes that the different angles of telling result from different underlying issues of identity and power.